THE INFLUENCE ON COMMUNITY-HEALTH AND FOODHYGIENE VIA ISOLATED SALMOMELLA FROM RAW-FOODS AND MORE-RECENT ANTIBIOTIC SENSITIVITY PATTERNS, TAIF, KSA - Sherifa Mostafa M. Sabra (Basrah Journal of Veterinary Research)
This work aimed to confirm "The influence Salmonella on community-health (CH) and food-hygiene (FH) in raw-foods (RFs) and More-recent (MR) antibiotic sensitivity patterns to Salmonella. In Taif, (KSA), the results was (35.0, 25.0, 17.5, 10.0, 7.5 and 5.0%) for Salmonella types (Non typhi group D, Para typhi group B, Para typhi group A, Para typhi group C, Salmonella Spp and Enteritidis), respectively. The effect of antibiotics were (CAX, CFT, C, CP, T/S and AM) as (98.8, 97.7, 87.3, 85.3, 65.7 and 48.5%) respectively. The scores were (100, 89.5, 84.0, 83.3, 76.5 and 66.7%) for Salmonella (Spp., Non typhi group D, Para typhi group B, Enteritidis, Paratyphi group A and Paratyphi group C), respectively. The excellent MR antibiotics were (CAX, CFT, C, CP and T/S), the effect ratios were given 100%. The good MR antibiotics were (C, CP, CAX, T/S, CFT and AM), the effect ratios were given (75-100%). The approved MR antibiotics were (Am, T/S, C and CP), the effect ratios were given (50-75%). The not approved MR antibiotics were (AM, T/S and AM), the effect ratios were given (under 50%). That concluded must take the hygienic precautions and healthy measures such as non-use of antibiotics in animal and bird rations, monitoring of (slaughter-houses, grocery, stores, fast food shops and their employees), making "Rapid Treatment System" for infected individuals is recommended. The "Protective Medicine Unit" and "Municipals Unit" belong to MOH must be immediately follow the food bacterial contamination sources for healthy eradication that to protect the CH and FH